2014
DOI: 10.4172/2329-6887.1000141
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the FDA Warning for Statins and Cognitive Dysfunction

Abstract: Background: The ACC/AHA released new guidelines in December of 2013 for treatment of high blood cholesterol to simplify identification and treatment of patients most likely to benefit from statins. These guidelines may result in more patients receiving statin therapy, and at younger ages. In 2012, the U.S. Food and Drug Administration (FDA) mandated warnings for all statin drugs for possible adverse effects on cognitive performance. Statins can be classified as having greater lipophilic or hydrophilic solubili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 60 publications
2
23
0
Order By: Relevance
“…It appears to be the reason why atorvastatin and simvastatin have higher association with non-hepatocytic adverse effects, such as cognitive impairment, compared to all other lipophilic statins [51,54]. Our findings of higher association of cognitive impairment with lipophilic atorvastatin were aligned with the other studies that have demonstrated higher association and severity of cognitive impairment with lipophilic statins compared with hydrophilic statins [11,21,46,[59][60][61][62].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…It appears to be the reason why atorvastatin and simvastatin have higher association with non-hepatocytic adverse effects, such as cognitive impairment, compared to all other lipophilic statins [51,54]. Our findings of higher association of cognitive impairment with lipophilic atorvastatin were aligned with the other studies that have demonstrated higher association and severity of cognitive impairment with lipophilic statins compared with hydrophilic statins [11,21,46,[59][60][61][62].…”
Section: Discussionsupporting
confidence: 84%
“…As such the voluntary reporting to the AERS by the physicians varies between 1% and 10%, which is considered as extremely low [49]. Extrapolation of the underreported data estimates that annually about 3,000 -30,000 adverse effects of cognitive impairments due to statins, especially simvastatin and atorvastatin, were not reported to the AERS [21]. Hence, our finding of significantly higher association of cognitive impairment in patients who were on HIST compared to the general population highlights the importance of an inclusive approach in the adverse effect assessment in the form of periodic assessment of cognitive function of patients who are on statin therapy, especially in patients who are on HIST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 However, another study also using FDA databases found that neurological disease was reported more often for lipophilic statins that more readily cross the blood-brain barrier, than for hydrophobic statins. 48 A meta-analysis of 23 randomised clinical intervention trials on statins reporting data on cognitive function in 29 012 participants failed to show adverse cognitive effects of statins and thus lower LDL .…”
Section: Other Studiesmentioning
confidence: 99%
“…Some epidemiological studies and meta‐analyses found no difference in effects on cognition when comparing lipophilic and hydrophilic groups, but others reported a beneficial effect of the lipophilic group . Yet others suggested a beneficial role of lipophilic statins in noncarriers of ApoEe4 or a harmful effect of lipophilic statins . Another study showed that use of lipophilic statins was associated with more favourable white matter structural integrity in older adults with lower cognitive performance but no dementia diagnosis .…”
Section: Medications With Potential Effects On the Brain Cholesterol mentioning
confidence: 99%